Integrasi Akuntansi sebagai Pondasi Keuangan dalam Manajemen Kas Usaha Mikro - Jedeot, Anskarina; Santi, Fitriana; Trisna June, Cindy Getah; Ary Yunita Anggraeni (University of Merdeka Malang, 2025)
This study explores the awareness of Micro, Small, and Medium Enterprises (MSMEs) regarding the importance of financial record-keeping and identifies the factors influencing such practices. Despite being a vital sector in Indonesia's economy, many MSME owners lack proper financial management skills, hindering business optimization and complicating access to formal financing. Using a qualitative method with a case study approach, data were collected through in-depth interviews with MSME owners from various sectors and direct observations of their financial management practices. Thematic analysis was employed to understand their awareness, experiences, and challenges in financial record-keeping. The findings show that financial record-keeping awareness remains low due to limited financial literacy, misconceptions that records are only needed for large businesses, and resource constraints such as time and knowledge. Additionally, mixing personal and business finances is a common issue, making it difficult to monitor cash flow and profits accurately. This study recommends targeted financial literacy programs for MSMEs and the development of simple, accessible financial recording tools. These efforts are expected to enhance MSME owners’ financial management capabilities, contributing to improved business sustainability.